Determinan Pemakaian Metode Kontrasepsi Jangka Panjang (MKJP) di Puskesmas Kecamatan Gunung Sindur Kabupaten Bogor Tahun 2020 - Hanny Desmiati; Nuntarsih Nuntarsih; Happy Novriyanti Purwadi (Indonesian Journal of Midwifery (IJM), 2022)
The government's efforts in dealing with the population growth rate in Indonesia is to hold it a national family planning program. The most effective method of birth control is a Long Term Contraception Method (LTM). LTM consumption in Indonesia is still less attractive to spouses of fertile age (EFA) and tends to decrease. This thesis aims to determine the factors associated with the use of Long-Term Contraception Method (LTM) at the District Health Center Mount Sindur Year 2017. The study design was cross-sectional with quantitative and qualitative approach using primary data with a total sample of 154 women of childbearing age. Data analysis by multivariate analyzes.The results obtained by the use of LTM in Gunung Sindur District Health Clinics in 2020 amounted to 31.2%. There is a relationship (p≤0,05) between education, occupation, number of children born alive, knowledge, attitudes, the role of health professionals, counseling, support a husband, a source of information. There is no relationship (p≥0,05) between age, number of children desired, a history of previous use of contraception, access to the location of health facilities, the role of neighbors / friends, the role of cadres. The most dominant factor in the use of LTM are resources with OR = 14.8, meaning that getting resources WUS has a 14.8 times greater chance of taking LTM compared WUS uninformed.Abstrak Upaya pemerintah dalam menangani laju pertumbuhan penduduk di Indonesia adalah dengan mengadakannya program KB nasional. Metode KB yang paling efektif adalah Metode Kontrasepsi Jangka Panjang (MKJP). Pemakaian MKJP di Indonesia masih kurang diminati oleh Pasangan Usia Subur (PUS) dan cenderung menurun. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan pemakaian Metode Kontrasepsi Jangka Panjang (MKJP) di Puskesmas Kecamatan Gunung Sindur Tahun 2020 .Desain penelitian adalah cross sectional dengan pendekatan mixed method menggunakan data primer dengan jumlah sampel sebanyak 154 wanita usia subur. Teknik analisa data dengan multivariat. Hasil penelitian diperoleh pemakaian MKJP di Puskesmas Kecamatan Gunung Sindur tahun 2017 sebesar 31,2%. Ada hubungan (p≤0,05) antara pendidikan, pekerjaan, jumlah anak lahir hidup, pengetahuan, sikap, peran tenaga kesehatan, konseling, dukungan suami, sumber informasi. Tidak ada hubungan (p≥0,05) antara umur, jumlah anak yang diinginkan, riwayat pemakaian kontrasepsi sebelumnya, akses lokasi fasilitas kesehatan, peran tetangga/ teman, peran kader. Faktor paling dominan dalam pemakaian MKJP adalah sumber informasi dengan nilai OR=14,8, artinya WUS yang mendapatkan sumber informasi mempunyai peluang 14,8 kali lebih besar memakai MKJP dibandingkan WUS yang tidak mendapatkan informasi.